Investigation of the effect of temperature on lithium-sulfur cell cycle life performance using system identification and x-ray tomography - Shateri, Neda; Auger, Daniel J.; Fotouhi, Abbas; Brighton, James; Du, Wenjia; Owen, Rhodri E.; Brett, Dan J. L.; Shearing, Paul R. (Wiley, 2022)
In this study, cycle life performance of a prototype lithium-sulfur (Li−S) pouch cell is investigated using system identification and X-ray tomography methods. Li−S cells are subjected to characterization and ageing tests while kept inside a controlled-temperature chamber. After completing the experimental tests, two analytical approaches are used: i) The parameter variations of an equivalent-circuit model due to ageing are determined using a system identification technique. ii) Physical changes of the aged Li−S cells are analyzed using X-ray tomography. The results demonstrate that Li−S cell's degradation is significantly affected by temperature. Comparing to 10 °C, Li−S cell capacity fade happens 1.4 times faster at 20 °C whereas this number increases to 3.3 at 30 °C. In addition, X-ray results show a significant swelling when temperature rises from 10 to 20 °C, correspondingly the gas volume increases from 13 to 62 mm3.
Keywords: egradation modelling; electrochemistry; energy conversion; lithium-sulfur battery; temperature; 3D gas thickness; X-ray tomography